Design and Simulation of Fuzzy Logic Controlled Car Parking Assist System - Ahmad Firdaus, A.Z.; Wei Shinn, Au; Hashim, M.S.M.; Khalid, N.S.; Ismail, I.I.; Ridzuan, M.J.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The simulation of the autonomous self-parking car model is introduced in this paper. The system using a fuzzy logic controller in monitoring the car into a parking spot. The car will be manoeuvred to the parking space along a curvilinear path called path planning that designed to prevent crashing with the neighbouring cars or obstacles. In this project, it has used the Simulink in MATLAB to compute the system. The Simulink has an easier way to set up the rules in fuzzy control. The system imitates human thinking in performing the parking whereby it controls the steering angle and speed of the car corresponded to the situation of the car.